(untitled) (Emancipação, 2014)
Analisa-se a relação dos catadores de resíduos sólidos domésticos com seu universo de trabalho, a fim de compreender quais possibilidades de inclusão e construção da cidadania podem ser vislumbradas. Realizou-se um estudo comparativo entre catadores do município de Estrela/RS, divididos em dois grupos: os trabalhadores da Unidade de Triagem de Lixo (UTL) e catadores de rua que atuam individualmente. A metodologia é qualitativa. As narrativas das entrevistas foram tratadas por meio da análise de conteúdo temática. Conclui-se que os catadores transformam-se em novos atores sociais da cadeia produtiva dos resíduos sólidos, mas o processo de construção de cidadania ainda éprecário, uma vez que os catadores permanecem sem seus direitos fundamentais básicos assegurados. Abstract: This article is the result of a study carried out with waste pickers which aims to analyze the relation of waste pickers and their work in order to understand the possibilities of inclusion and how citizenship can be constructed. A comparative study was developed among the waste pickers from Estrela/RS divided into two groups: the workers from the Garbage Sorting Unit (in the English acronym) and the waste pickers who work on their own on the streets. The study used a qualitative methodology which included the content analysis of interviews. The outcomes of the study demonstrate that waste pickers become new social actors of a productive chain of recycling material, but the study also demonstrates that the construction of citizenship is still unstable as the fundamental rights of waste pickers are still not provided. Keywords: Waste pickers. Citizenship. Social representations.